In vivo chromatin accessibility correlates with gene silencing in Drosophila. - Boivin, A.; Dura, J.M. (Genetics, 1998)
Gene silencing by heterochromatin is a well-known phenomenon that, in Drosophila, is called position effect variegation (PEV). The long-held hypothesis that this gene silencing is associated with an altered chromatin structure received direct support only recently. Another gene-silencing phenomenon in Drosophila, although similar in its phenotype of variegation, has been shown to be associated with euchromatic sequences and is dependent on developmental regulators of the Polycomb group (Pc-G) of gene products. One model proposes that the Pc-G products may cause a local heterochromatinization that maintains a repressed state of transcription of their target genes. Here, we test these models by measuring the accessibility of white or miniwhite sequences, in different contexts, to the Escherichia coli dam DNA methyltransferase in vivo. We present evidence that PEV and Pc-G-mediated repression mechanisms, although based on different protein factors, may indeed involve similar higher-order chromatin structure.